Planear una metodología con la cultura 5s´S para mejorar la productividad de una industria metalmecánica - Bermeo González, Mauricio José (2010)
The implementation of the 5S s methodology of the quality in the production plant Somirco Cía. Ltda., took place during the period between March 20th and May 19th 2009. Activities were completed according to our presented schedule; these aimed at developing an organizational culture of order, cleanliness, standardization and discipline on behalf of all operative staff. For this effect we trained and worked with all staff to obtain a greater benefits and efficiency. Additionally, working and action zones were marked. Final production and ex-works locations were created. The work chain was relocated and the plant’s distribution was redesigned. We placed signs identifying security zones. Cleaning days were established and the staff´s working conditions were largely improved.